CONTRIBUTION OF MATHEMATICS LEARNING MOTIVATION TO STUDENTS' MATHEMATICS LEARNING OUTCOMES IN JUNIOR HIGH SCHOOL - Usman, Patima M (JURNAL PENDIDIKAN GLASSER, 2024)
Students who have great motivation and create positive perceptions in mathematics lessons will improve student learning outcomes. However, the learning motivation of class VIII students at SMP Negeri 3 Luwuk in mathematics is still low. Therefore, this research aims to determine the contribution of mathematics learning motivation to mathematics learning outcomes in class VIII students at SMP Negeri 3 Luwuk, while the research was carried out from May to June 2021. In this research, the variables to be studied consist of 2 variables, namely variables X and Y, where the motivation to learn mathematics is placed in variable Luwuk. The data collection methods used are observation, questionnaires, tests and documentation. The analysis used is product moment correlation. The research results show that the correlation coefficient (r) = 0.3598 or 35.98% is a positive number. This shows that the contribution of mathematics learning motivation to the mathematics learning outcomes of class VIII students at SMP Negeri 3 Luwuk is positive and the interpretation is between 0.20 - 0.399 which is interpreted as a low level of influence. The KD value = 12.96% shows the low influence of the contribution of mathematics learning motivation to the mathematics learning outcomes of class VIII students at SMP Negeri 3 Luwuk, amounting to 12.69%. Meanwhile, the value of tcount = 1.6808 with degrees of freedom (db) = 21-2 = 19 with a significance level of 0.05 = 2.093 so tcount is less than ttable or 1.6808 < 2.093, so the correlation that occurs is meaningless or not significant so The correlation is that there is no contribution of mathematics learning motivation to the mathematics learning outcomes of class VIII students at SMP Negeri 3 Luwuk. Thus the hypothesis is rejected.